Odpowiedzi

2010-02-09T19:35:53+01:00
-x+3y=8
2x-y=-6

x=3y-8
2(3y-8)-y=-6
6y-16-y=-6
5y=-6+16
5y=10
y=10:5
y=2

x=3y-8=3×2-8=6-8=-2
była to metoda podstawiania
spr. 2+3×2=8
8=8

2×-2-2=-6
-6=-6
1 4 1
2010-02-09T19:40:26+01:00
-x + 3y =8
-y= -6 - 2x

-x + 3y =8
y=6 + 2x

-x + 3(6+2x) =8
y= 6 + 2x

-x + 18 + 6x =8
y = 6 + 2x

5x = -10
y = 6 + 2x

x = -2
y = 6 + (-4)

x= -2
y= 2
Pozdrawiam!
1 4 1
2010-02-09T19:41:45+01:00
-x+3y=8 /*2
2x-y=-6

-2x+6y=8
2x-y=-6
5y=2 /:5

y=2½
-x=8-3y

y=2½
-x=8-3*2½

y=2½
-x=½ /*(-1)

x=-½
y=2½
1 4 1